Physical characteristics and chemical compositions of the essential oils extracted from different parts of Siphonochilus aethiopicus (Schweinf.) B. L.Burtt (Zingiberaceae) harvested in Benin - NOUDOGBESSI, JEAN PIERRE AKODOGBO; YEDOMONHAN, HOUNNANKPON; ALITONOU, GUY ALAIN; Chalard, Pierre; FIGUEREDO, GILLES; ADJALIAN, Elvis; AVLESSI, FÉLICIEN; CHALCHAT, Jean C.; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2012)
The chemical composition of essential oils of limbo, foliar sheath and rhizomes Siphonochilus aethiopicus by hydrodistillation was investigated by GC / MS. Curzerenone (12.9-51.9%), b-pinene (6.7-44.5%), intermedeol (8.0- 31.7%), a-humulene (6.4-25.8%), caryophyllene oxide (4.9-25.4%), palmitic acid (13.6%), tetradecanoate ethyl (12.8%), a-cadinol (12.0%), methyl salicylate (9.9%) and geranyl octanoate (5.8%) were the major compounds of the essential oils studied, but they do not characterize specifically a particular organ of the plant. Significant differences were observed between the values of density, refractive index and rotatory power determined by standard methods (AFNOR) in essential oils. These values of the density, rotatory power and the refractive index will contribute to a better characterization of the essential oils of this plant.
Keywords: S. aethiopicus; curzerenone; b-pinene; physical characteristics